The effects of job satisfaction and organizational commitment on organizational citizenship behavior - Arif Partono Prasetio; Syahrizal Siregar; Bachruddin Saleh Luturlean (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2015)
The service quality is always the main factor for organization which focuses on the customer satisfaction to enhance their business and their performance. In order to have the great quality, they depend on their human resources. They need human resources who perform well. The employee who shows strong Organizational Citizenship Behavior believed can be performs better. That is why it is important for the organization to create employee with the strong OCB. OCB influenced by various factors. Job satisfaction and organization commitment are two important factors among them, which can predict the OCB. Organization should maintain the level of their employee’s satisfaction and commitment in order to develop the strong OCB. The research analyzed the effect of the job satisfaction and organization commitment on OCB at the PLN Distribution Office for Wet Java and Banten. Research conducted towards 100 participants using the multiple regression and descriptive analysis method. Through the analysis we found that job satisfaction and organization commitment has significance relation toward OCB (0.516). This finding is in line with previous research which promotes positive relation between these variables, eventhough only a mild percentage (0.266).The organization should place detail attention when applying the treatment. We suggest that the both job satisfaction and organization commitment should apply simultaneously in order to get better result. Further research needed to identify others factor which might be important to enhance the OCB.